Implementasi Moderasi Beragama Dalam Tradisi Semaan Al-Qur’an Komunitas Santri Urban: Studi Organisasi Jam’iyyatul Qurra Wal Huffaz Nahdlatul Ulama (JQH NU) - Khoirul Anwar, Koirul Anwar (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
The tradition of reading the Qur’an carried out by JQH members reflects the actions of Al-Qur’an lovers in urban areas. The problem is to what extent does this action also correlate with the Indonesian Ministry of Religion’s for Religious Moderation (MB) and is it implemented in what ways? This research uses qualitative methods involving the theory of Al-Qur’an lovers offered by Farid Essack which can be seen from three categories. First, uncritical lover. Second, the scholarly lover. Third, the critical lover. The results of this research show that in the domain of Al-Qur’an lovers, JQH members show more attention to the first category by using the Al-Qur’an as reading material with edicative value. The implementation of religious moderation (MB) seen from the members can be mapped into four indicators: first, preserving traditions through a community forum for memorizing the Qur’an, the majority of whom come from the regions of pheriperal. Second, through learning the Qur’an which prioritizes the sanad tradition by each member. Third, preserving edicative activities to celebration of the national holidays. Fourth, have a sub-cultural religious perspective.